O specyfice włoskich tekstów prasowych - Dykta, Dominika; Marcol-Cacoń, Lucyna (Scripta Neophilologica Posnaniensia, 2022)
The purpose of the article is to present the characteristics of the language of current Italian press texts. The theoretical issues were supported by examples taken from Italian newspapers. The problem of the language of Italian press texts was discussed, first, by Bonomi and De Blasi, whose works were the inspiration to write the present article. The operations like direct speech, borrowings from colloquial language, neologisms, anglicisms, collocations, frase scissa, dislocazione a sinistra and c’è presentativo were discussed. These measures are intended to simplify and make the language of the press more attractive, and thus make the Italian press language more accessible to the average Italian audience. This study may be of assistance, above all, to those students of Italian language who deal with the issues of translation of press texts during their classes. Some selected linguistic phenomena, supplemented by examples, have been chosen in such a way as to develop the reception and production of the press texts in the Italian language.